Viral hepatitis C during a screening campaign in general population of Benin: seroprevalence and associated factors - KPOSSOU, A R (My University, 2021)
Introduction: Hepatitis C is a global public health problem. The purpose of this study was to determine the prevalence and factors associated with hepatitis C virus (HCV) antibody carriage during mass screening in several localities throughout Benin. Methods: This was a descriptive and analytical cross-sectional study with prospective data collection. This collection took place from 20 to 28 July 2019 at a free voluntary hepatitis C screening organized in Benin by Rotary Clubs in 23 sites throughout the country. A rapid diagnostic orientation test was used for the detection of anti-HCV antibodies. Results: A total of 9035 voluntary participants were included, mostly of Beninese nationality (99.0%), with a median age of 27 years, of whom 51.1% (4619/9035) were single and mainly schoolchildren, pupils or students (37.9%; 3426/9035). HCV seroprevalence was 1.0% (87/9035) [95% CI= 0.8% - 1.2%]. This infection was associated with age greater than 42 years (ORa=2.71 ; 95% CI : 1.06 - 6.95) , p<0.03, and history of diabetes (ORa=3.9; 95% CI: 1.9-7.6). Conclusion: HCV antibody seroprevalence is relatively low in the study population: 1%. Factors associated with HCV antibody carriage were age, occupation and diabetic history
Keywords: hepatitis C virus; Epidemiological profile; Bénin